2019
DOI: 10.4310/joc.2019.v10.n2.a1
|View full text |Cite
|
Sign up to set email alerts
|

On the boundary of the region defined by homomorphism densities

Abstract: The Kruskal-Katona theorem together with a theorem of Razborov [Raz08] determine the closure of the set of points defined by the homomorphism density of the edge and the triangle in finite graphs. The boundary of this region is a countable union of algebraic curves, and in particular, it is almost everywhere differentiable. One can more generally consider the region defined by the homomorphism densities of a list of given graphs, and ask whether the boundary is as well-behaved as in the case of the triangle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Regarding our results on the shape of Ω(F), there are (at least) two previous works of a similar flavor: Razborov [22] determined the closure of the set of points defined by the homomorphism density of the edge and the triangle in finite graphs (and showed that the boundary is almost everywhere differentiable) and Hatami-Norine [8] constructed examples which show that the restrictions of the boundary to certain hyperplanes of the region defined by the homomorphism densities of a list of given graphs can have nowhere differentiable parts.…”
Section: Introductionmentioning
confidence: 58%
“…Regarding our results on the shape of Ω(F), there are (at least) two previous works of a similar flavor: Razborov [22] determined the closure of the set of points defined by the homomorphism density of the edge and the triangle in finite graphs (and showed that the boundary is almost everywhere differentiable) and Hatami-Norine [8] constructed examples which show that the restrictions of the boundary to certain hyperplanes of the region defined by the homomorphism densities of a list of given graphs can have nowhere differentiable parts.…”
Section: Introductionmentioning
confidence: 58%
“…For larger graphs the problem becomes extremely challenging. Some general results on the hardness of determining T (F) were obtained by Hatami and Norine in [16,17].…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to Theorem 1.2 Hatami and Norin [ 9 ] gave an example of a finite family F of graphs such that the intersection of the graph profile T pFq with some hyperplane has a nowhere differentiable boundary.…”
Section: General Resultsmentioning
confidence: 99%